A temporal force analysis of the crawl arm stroke during thethered swimmig - Goldfuss, A. J.; Nelson, R. C. (First International Symposium on "Biomechanics and Swimming, Waterpolo and Diving", 14-16 September 1970. Proceedings, 1971)
Since swimming is an activity in which distance is covered in the pool, it has not been technically feasible to film nor to attach various measuring devices to the swiwmer over the total course of his performance. In an attempt to alleviate this problem, research has been directed toward studies of tethered swiwming ; a method of performance in which the swimmer was attached to a stationary object or force~~easuring device by means of a cable or pulley system, causing him to swim in place, at zero velocity. Since tethered swimming offers a favorable situation for measurement, it is possible to employ instrumentation that would measure several components of movement simultaneously. The present investigation was an initial attempt to combine forcemeasuring apparatus with cinematography to measure force and temporal aspects of the crawl arm stroke. The temporal analysis included measurement of the time taken to execute selected phases of the arm stroke above and below the water, and the changes in time that occurred during each of these phases over a two-minute, all-out, tethered swim. The force analysis included the measure of maximum force and the determination of its occurrence in the stroke cycle.